Entwicklungslinien und Entwicklungsperspektiven im Mobiliarsicherungsrecht - Faber, Wolfgang (Jan Sramek Verlag, 2023)
This book analyses main lines of legal development in the area of proprietary security rights in movable assets (comprising pledges/charges, transfer of ownership for security purposes, assignment of claims for security purposes, and retention of title), starting from Roman law through the era of European codifications up to the present law in particular in Austria, then continues by analysing main questions of this area of law - above all isues concerning registration systems for security rights - in Germany, the Netherlands, France, Belgium and England, and finally analyses, on that basis, whether the "Draft Common Frame of Reference" (DCFR), presented by an international group of experts in 2009, provides adequate solutions which are suitable to continue these legal developments consequently. The results achieved in this research show that the DCFR offers attractive solutions that are apt for the future development of the law in almost all areas investigated.